Acoustic and thermal performances assessment of sustainable insulation panels made from cardboard waste and natural fibers. (October 2022) - Ouakarrouch, Mohamed; Bousshine, Said; Bybi, Abdelmajid; Laaroussi, Najma; Garoum, Mohammed
Highlights: Elaborate and characterize new ecological acoustic absorbers/sound insulation panels and thermal insulation panels. Acoustic and thermal properties were measured experimentally using standardized methods. Morphological analysis of the different fibers was carried out using scanning electron microscopy. Bulk density, air flow resistivity and water absorption were measured experimentally. The new panels are good candidates for the development of local materials with the required acoustic and thermal properties. Abstract: This work aims to elaborate and characterize new ecological composite materials from cardboard waste and abandoned natural fibers for the manufacture of local acoustic absorbers/sound insulation panels and thermal insulation panels. For this purpose, twenty-eight samples were prepared by mixing a mass fraction of 60 % of cardboard waste and 40 % of natural fibers available in the south-east region of Morocco, i.e. Doum, Wheat straw, Reed, Esparto, Bagasse, Fig, and Olive. Firstly, the morphological analysis of the different fibers was carried out by scanning electron microscopy (SEM). Secondly, the acoustic and thermal properties were measured experimentally using standardized methods. In addition, bulk density, air flow resistivity and water absorption were measured. The experimental results showed that the studied panels have good acoustic and thermal performances. The sound absorption coefficient, sound transmission loss, bulk density, thermal conductivity, and heat capacity were in the range of 0.4–0.8; 20–45 dB; 278.6–343.8 kg/m 3 ; 0.072–0.10 W/m.K; 1254.5–1807.5 J/kg.K, respectively. Consequently, the new panels developed in this study are good candidates for the development of local materials with the required acoustic and thermal insulation properties for applications in buildings. Their main advantages are: low environmental impact, low cost, and they can even compete with commercialized synthetic materials.